2020
DOI: 10.1002/cac2.12085
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic alterations identifies the frequent mutation of GNAS in colorectal laterally spreading tumors

Abstract: of genetic alterations identifies the frequent mutation of GNAS in colorectal laterally spreading tumors Dear Editor, Colorectal cancer (CRC) is among the most commonly diagnosed cancer and the leading cause of cancer-related death worldwide [1]. Most CRCs develop from adenomas. Laterally spreading tumors (LSTs) are non-polypoid superficial colorectal neoplasms (CRNs) that are larger than 1 cm and typically extend laterally along the luminal wall. Based on surface morphology, it can be classified into a granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The difference in rates between the specimens was not statistically significant and the results were consistent with other reported APC mutation rates of 15.5%-42.4% in LST specimens. Two recent studies showed APC mutation frequencies of 80% (10 samples) and 57% (14 samples) in LST[ 15 ]. Therefore, APC mutation may act as an important initiator in LST development[ 16 ].…”
Section: Truncated Apc Mutationmentioning
confidence: 99%
“…The difference in rates between the specimens was not statistically significant and the results were consistent with other reported APC mutation rates of 15.5%-42.4% in LST specimens. Two recent studies showed APC mutation frequencies of 80% (10 samples) and 57% (14 samples) in LST[ 15 ]. Therefore, APC mutation may act as an important initiator in LST development[ 16 ].…”
Section: Truncated Apc Mutationmentioning
confidence: 99%